2020
DOI: 10.3389/fnhum.2020.00155
|View full text |Cite
|
Sign up to set email alerts
|

Resting State EEG in Exercise Intervention Studies: A Systematic Review of Effects and Methods

Abstract: Background: Exercise has been shown to alter brain plasticity and is explored as a therapeutic intervention in a wide variety of neurological diseases. Electroencephalography (EEG) offers an inexpensive method of studying brain electrocortical activity shortly after exercise and thus offers a way of exploring the influence of exercise on the brain. We conducted a systematic review to summarize the current body of evidence regarding methods of EEG analysis and the reported effects of exercise interventions on E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(28 citation statements)
references
References 92 publications
0
28
0
Order By: Relevance
“…Power spectral density values were calculated in four midline ROIs assigned as frontal (FCz, FC1, FC2, Fz, F1, F2), central (Cz, C1, C2, CPz, CP1, CP2), parietal (Pz, P1, P2, POz, PO3, PO4) and occipital (Oz, O1, O2). Even though previous analyses revealed that changes in EEG power in response to exercise did not indicate systematic region-specific effects, the assignment to ROIs was done to provide a more specific description of brain activity in response to exercise compared to the global PSD values (Crabbe and Dishman 2004;Gramkow et al 2020).…”
Section: Eeg Power Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Power spectral density values were calculated in four midline ROIs assigned as frontal (FCz, FC1, FC2, Fz, F1, F2), central (Cz, C1, C2, CPz, CP1, CP2), parietal (Pz, P1, P2, POz, PO3, PO4) and occipital (Oz, O1, O2). Even though previous analyses revealed that changes in EEG power in response to exercise did not indicate systematic region-specific effects, the assignment to ROIs was done to provide a more specific description of brain activity in response to exercise compared to the global PSD values (Crabbe and Dishman 2004;Gramkow et al 2020).…”
Section: Eeg Power Analysismentioning
confidence: 99%
“…Further, EEG data recorded in response to incremental cycling exercise reveal bidirectional modulations of cortical activation in the frontal and sensory cortex (Brümmer et al 2011;Robertson and Marino 2015). Interestingly, these modulations of regional EEG activity seem to even persist at rest after exercise, but do not reveal a clear intensity-dependent regionspecific or frequency-specific pattern (Crabbe and Dishman 2004;Gramkow et al 2020). Taking into account that the human brain is characterized by functional integration of multimodal information from regionally distinct brain areas by means of large-scale networks (Fox et al 2005), the analysis of regional activity levels may not sufficiently reflect exercise-induced modulations of cortical mechanisms and could explain these heterogeneous findings.…”
Section: Introductionmentioning
confidence: 99%
“…While the interaction of acute endurance exercise and the cardiovascular system is well understood, research in the last decade started to rather unfold the effect of acute and long-term exercise on the central nervous system 1 3 . Thus, growing evidence suggests that metabolic changes induced by exercise are associated with systematic modulations of brain function due to neurochemical changes within the central nervous system 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus, growing evidence suggests that metabolic changes induced by exercise are associated with systematic modulations of brain function due to neurochemical changes within the central nervous system 2 . Several neuroimaging studies have shown that these acute changes induce modulations of brain function that persist at rest after exercise cessation 1 . Hereof, the use of electroencephalography (EEG) appears feasible for field-application due to its fast applicability, high degree of mobility and excellent temporal resolution 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation